Uji Aktivitas Antibakteri Fraksi N-Heksana Ekstrak Etanol 96% Daun Pare (Momordica charantia L.) Terhadap Bakteri Staphylococcus epidermidis - Rabiatul Munawarah; Putri Kartika Sari; Eka Fitri Susiani (BORNEO JOURNAL OF PHARMASCIENTECH, 2023)
Pare leaves (Momordica charantia L.) have many health benefits. Leaves pare (M.chrantia L.) are a trusted herb that is used as an antibacterial plant. N-hexane fraction of pare leaves(S. epidermidis). The purpose of this study is to identify the secondary metabolite compounds found in the n-hexane fraction of ethanol extract 96% of pare leaves (M.charantia L.) and to find out the N-hexane fractions of etanol 96% pare leaves (M.charantia L.) in inhibiting S.epidermidis bacteria. The type of research is experimental. The leaf extraction process uses maseration with 96% ethanol solvent and fraxination using n-hexane solvent. Phytochemical screening tests include flavonoids, alkaloids, saponins, steroids/terpenoids, phenols and tannins. The antibacterial activity carried out using well method with concentration of 1%, 2%, 3% and 4%. The results of this study showed that a fraction of n-hexane ethanol extract 96% of the leaf (M.charantia L.) contained flavonoid, alkaloid and steroid compounds. The n-hexane fraction ethanol extract 96% leaf (M.charantia L.) has antibacterial activity in inhibiting the S.epidermidis bacteria in the weak to strong category. Based on the results, it can be concluded that the fraction n-hexane ethanol extract 96% of the leaf (Momordica charantia L.) is able to inhibit the bacteria S.epidermidis at all concentrations.